Intruder messaging system / Mohamad Muslim Rameli, Mohamad Arif Hanafi Mohd Sadan & Amer Akhmal Mohamed Hamdan - Rameli, Mohamad Muslim; Mohd Sadan, Mohamad Arif Hanafi; Mohamed Hamdan, Amer Akhmal (2015)
The Intruder Messaging System (IMS) is a system that can control some of home appliances through short messaging system (SMS) from the user mobile phone. The components that being used in this project is not too expensive and easily to be installed. It can save the user financial and more things to focus on their job. The components and the circuit have been optimized by using Fritzer Simulation software. The design prototype has been fabricated on Donut Board and the output was recorded by using the devices that were used. It show that the buzzer that work as a siren will ON their sound and a message was received on the phone when the PIR sensor detect a motion. The user also can send SMS to the circuit so that it can turn OFF the buzzer, and turning ON/OFF indoor and outdoor lighting.